Environmental law - Benidickson, Jamie (Essentials of Canadian Law, 2019)
"The fifth edition of Environmental Law, is a comprehensive introductory guide to environmental law in Canada which incorporates discussion of recent developments in environmental litigation and regulation alongside reference to key statutory developments from the past half decade. In addition, updating and revisions highlight significant developments in several key areas, notably federal and provincial climate change action following the 2015 Paris Agreement and issues associated with Aboriginal consultation, the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) and traditional environmental knowledge."-- Provided by publisher.